Interactive graphics for functional data analyses. Issue 1 (31st March 2016) - Wrobel, Julia; Park, So Young; Staicu, Ana Maria; Goldsmith, Jeff
Abstract : Although there are established graphics that accompany the most common functional data analyses, generating these graphics for each dataset and analysis can be cumbersome and time‐consuming. Often, the barriers to visualization inhibit useful exploratory data analyses and prevent the development of intuition for a method and its application to a particular dataset. Therefund.shiny package was developed to address these issues for several of the most common functional data analyses. After conducting an analysis, theplot_shiny() function is used to generate an interactive visualization environment that contains several distinct graphics, many of which are updated in response to user input. These visualizations reduce the burden of exploratory analyses and can serve as a useful tool for the communication of results to non‐statisticians. Copyright © 2016 John Wiley & Sons, Ltd.